Modeling of Irregularly Shaped Two – Dimensional Objects - Keyan, Arthur J. (Mathematical Problems of Computer Science, 2021)
In this paper the description of the two - dimensional modeling program of irregularly shaped objects is given. The program is very easy to use, it works fast and has many other advantages.